THE EFFECT OF FAMILY FUNCTIONING AND PEER CONFORMITY ON VERBAL BULLYING BEHAVIOR IN EARLY ADOLESCENCE - Prasasti, Putri Maulani Sri; Rahayuningsih, Idha; Puspitaningrum, Noer Suci Endah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Verbal bullying among early adolescents represents one of the most pervasive behavioral problems in school environments and is strongly associated with family dynamics and peer group influences. Adolescents who experience poor family functioning often lack emotional regulation and empathy, while high peer conformity increases their susceptibility to negative social behaviors, including verbal aggression. This study aims to examine the effect of family functioning and peer conformity on verbal bullying behavior among early adolescents. A quantitative correlational research design was employed, involving 120 students aged 12–15 years from several junior high schools in Gresik Regency. Data were collected using three validated instruments: the Family Assessment Device (FAD), the Peer Conformity Scale, and the Verbal Bullying Behavior Scale. Data analysis was conducted using multiple regression analysis with SPSS 26. The results indicate that both family functioning and peer conformity significantly influence verbal bullying behavior, with peer conformity showing a stronger predictive effect. Dysfunctional family environments and excessive peer conformity were found to increase the likelihood of adolescents engaging in verbal bullying. These findings highlight the importance of strengthening family communication patterns and promoting assertive peer norms to prevent aggressive verbal behavior in school contexts.